"Sonny’s Blues": The Dream Variation and Cultural Integration through Music - Sharma, Manahari (Bon Voyage, 2023)
“Sonny’s Blues” is a chronicle of racial prejudice, diverse dreams, suffering, redemption, and reconciliation. As a tale of conflicting relationships between two brothers in Harlem society, it narrates the narrative of life, liberty and the pursuit of happiness on two opposite sides that the brothers are situated in: the legacy of African-American cultural and mainstream dreams. It is against this background dichotomy that the suffering of Sonny, the African-American protagonist, engendered due to his latent desire to be a jazz musician, is shown. This paper discourses on the existential narrative and its manifestation on society through an individual and answers different questions: why would characters go through extreme familial tension? What aspires them to embody two dissimilar legacies? How does music amidst racism produce a therapeutic effect? How are human predicaments resolved and why do characters go back to their original niche, which their ancestors had created? Hence, this paper aims at how music outcasts the barriers and welcomes avenues of resilience by removing the thundering cloud of stillness and darkness in the blue sky of Harlem.